Development and evaluation of a baseline‐event‐anticipation score for hepatitis delta. Issue 11 (27th March 2014) - Calle Serrano, B.; Großhennig, A.; Homs, M.; Heidrich, B.; Erhardt, A.; Deterding, K.; Jaroszewicz, J.; Bremer, B.; Koch, A.; Cornberg, M.; Manns, M. P.; Buti, M.; et al.
Summary Hepatitis delta is considered the most severe form of viral hepatitis, but variables associated with disease progression are poorly defined. This study aimed to identify risk factors associated with worse clinical outcome in patients with hepatitis delta and to develop a clinical score to determine their risk of experiencing liver‐related morbidity or mortality. We followed 75 HBsAg–anti‐HDV‐positive patients with hepatitis delta for up to 16 years (median 5 years). The baseline‐event‐anticipation score (BEA score) was developed based on variables associated with the development of liver‐related clinical complications. Age, region of origin, presence of cirrhosis, albumin, INR, hyperbilirubinemia and thrombocytopenia were all associated with the development of an event in the training cohort. The BEA score included age, sex, region of origin, bilirubin, platelets and INR. Points were allocated according to hazard ratios, and three risk groups were defined: BEA‐A mild risk, BEA‐B moderate risk and BEA‐C high risk. Hazard ratios of BEA‐B and BEA‐C patients for liver‐related clinical endpoints were 9.01 and 25.27 vs BEA‐A with an area under curve of the receiving operating characteristic curve of 0.88. The accuracy of the BEA score was confirmed in two independent validation cohorts followed in Barcelona (n = 77) and Düsseldorf (n = 62). Delta hepatitis is associated with a very severe long‐term outcome. The BEA score is easy to apply and predicts with a very high accuracy the development of liver‐related complications in patients with hepatitis delta.